Life cycle impact assessment of the average passenger vehicle in the Netherlands. - Castro, Maria B.G.
Goal, Scope and Background. In this article, the Life Cycle Impact Assessment of the average passenger vehicle of the Netherlands is performed, with emphasis on the current dismantling and recycling practice in this country. From calculations on recovery rates of the several material streams from ELV (End of Live Vehicle)recycling, it seems that attaining the European ELV legislation recycling targets (Directive 2000/53/EC 2000) is very difficult, even for countries with advanced collection and recycling infrastructures such as the Netherlands. An LCA of the current average passenger vehicle of the Netherlands, including a detailed modelling of the recovery and recycling should form a sound basis for comparison with alternative automotive life cycle designs and legislation efforts. Model and System Definition. An average passenger vehicle is defined, having average weight and material composition. A cradle to grave approach is taken, including all relevant upstream processes for the production of materials and fuels, and the return of the recycled materials to the material cycles in the EOL (End of Life) phase. A particularity of this model is the detailed description of the Dutch collection and recycling infrastructure, with current data for the shredding, separation and metallurgical recycling processes. Results and discussion. According to the Eco-Indicator 99 (EI99), the largest environmental impact of the passenger vehicle's life cycle occurs i the use phase over 90 percent -, due to the combustion and depletion of fossil fuels. This is in agreement of previous studies. Also in the other life cycle phases, the use of fossil fuels is the dominant impact, even for the production phase. Resource depletion due to the use of the materials employed in the vehicle causes a comparatively lower environmental impact, namely due to the high recovery rate and efficiency of the metallurgical recycling, that balances for about 30 percent the total impacts of the materials production and use. NOx emission was one of the smallest emissions to air in quantity, but was responsible for 36 percent of the impact of the life cycle, while CO2 was the largest emission to air but caused only 6 percent of the environmental impact. Conclusion and Recommendation. Although there is a growing awareness and concern on increasing the recyclability of vehicles, the use phase still has the largest environmental impact of the vehicle's life cycle. A life cycle assessment can be a sound basis to evaluate and compare design alternatives to increase the sustainability of passenger vehicles. The ASR (Automotive shredder residue) is currently the greatest concern with regard to the recovery targets. It is a large amount of materials (about 32 wt percent), difficult and costly to recycle, and thermal recovery is limited to a maximu of 15 wt percent in 1015 by the European ELV legislation. Joint efforts from the automotive industry and legislative institutions are required to find a sensible solution. LCA can be a useful tool to support legislative decisions, as purely weight based recovery definitions are not adequate to evaluate the sustainability of the automobile lifecycle.
Keywords: Eco-indicator.; Emissions; Environmental impact; End-of-life (EOL).; End of live vehicle (ELV).; LCA; Life cycle impact assessment (LCIA).; Recycling; Resources; Passenger vehicles